FIND THE ANSWERS

What is the answer to sqrt(x^2-3x-6)=x-1?

Answer this question

Do you know the correct answer? Make money answering questions! Join now.
  • What is the answer to sqrt(x^2-3x-6)=x-1?


Answers

Solve this: $$\sqrt{x^2+3x+6}+\sqrt ... Mathematics Stack Exchange is a question and answer site for people studying ... $x=(-1\pm\sqrt6)/2\lor x=2(1\pm ...
Read more
Positive: 51 %
... differentiate using the chain rule. f'(x)=1/2(x^2+3x+6)^(-1/2)*d/dx ... tangent line at x=-1: graph{(y-sqrt(x^2+3x+6))(y-2 ... sentence answer ...
Read more
Positive: 48 %

More resources

... (x-1) / (x+1) > (x + 3) / (2x + 3)(x-1)(2x+3 ... (2x+3)-(x+3)(x+1)>0 x^2-3x-6>0 x=(3+sqrt{33})/2 or =(3-sqrt{33})/2. anonymous; 5 years ago (x-1) / (x+ ...
Read more
Positive: 51 %
(x-1)(2x+3)-(x+3)(x+1)>0 x^2-3x-6>0 x=(3+sqrt{33}) ... Answer is x > 1/2( 3 +sqrt(33) anonymous; 5 years ago. x 1/2(3 - sqrt ...
Read more
Positive: 46 %
Math 220 February 21 ... Answer: f0(x) = 1 2 p x2 + 3x+ 6 (x2 + 3x+ 6)0 = 1 2 p x2 + 3x+ 6 (2x+ 3) = ... Answer: f 0(x) = 1 2(x+ p x+ p x+ 1) (x+ q x+ p x+ ...
Read more
Positive: 32 %
Answer to What is the value of x in the equation −x = 2 − 3x + 6? ... y−7=−23(x+1)y−7=−23(x+1) y−7=23(x−1)y−7=23(x−1) y+7=−23(x−1 ...
Read more
Positive: 9 %

Show more results